2022
DOI: 10.3390/v14091916
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity of COVID-19 Vaccination with ChAdOx1 nCoV-19 Following Previous SARS-CoV-2 Infection: A Humoral and Cellular Investigation

Abstract: Infections caused by SARS-CoV-2 induce a severe acute respiratory syndrome called COVID-19 and have led to more than six million deaths worldwide. Vaccination is the most effective preventative measure, and cellular and humoral immunity is crucial to developing individual protection. Here, we aim to investigate hybrid immunity against SARS-CoV-2 triggered by the ChAadOx1 nCoV-19 vaccine in a Brazilian cohort. We investigated the immune response from ChAadOx1 nCoV-19 vaccination in naïve (noCOVID-19) and previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Despite individuals who were previously infected and received two doses of CoronaVac showing a slower decline compared to ChAdOx1, their binding antibody levels and neutralizing activities remained at a low titer six months after vaccination [ 36 ]. Conversely, a single dose of ChAdOx1 exhibited robust antibody and neutralizing activity that was consistent with those reported in previous studies [ 14 , 37 ], while a second dose did not clearly enhance the immune response in individuals with prior infection. Similar results were found in mRNA vaccination, indicating that immunization with a single dose significantly boosted the expansion of pre-existing memory B cells in individuals with prior infection, while minimal changes in antibody response was observed after a second dose [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite individuals who were previously infected and received two doses of CoronaVac showing a slower decline compared to ChAdOx1, their binding antibody levels and neutralizing activities remained at a low titer six months after vaccination [ 36 ]. Conversely, a single dose of ChAdOx1 exhibited robust antibody and neutralizing activity that was consistent with those reported in previous studies [ 14 , 37 ], while a second dose did not clearly enhance the immune response in individuals with prior infection. Similar results were found in mRNA vaccination, indicating that immunization with a single dose significantly boosted the expansion of pre-existing memory B cells in individuals with prior infection, while minimal changes in antibody response was observed after a second dose [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, existing evidence has largely focused on the early response following mRNA vaccination among previously infected individuals [ 10 , 11 , 12 , 13 ]. Few studies have evaluated the impacts of inactivated and vector-based vaccines [ 14 , 15 , 16 ]. Additionally, most investigations have focused on short-term immunogenicity, while long-term evaluations remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, De Marcos and co-authors [ 37 ] found no difference in cellular immune response to the Omicron variant in a cohort of naïve or SARS-CoV-2–infected vaccinated health workers. In Brazil, Azamor and co-authors [ 68 ] found that 120 days after the second dose of ChAadOx1 nCoV-19, the percentages of CD4+ and CD8+ T cells were higher in a non-infected SARS-CoV-2 group compared with an infected SARS-CoV-2 group. Our results of cellular immune responses in the naïve group and the SARS-CoV-2 patients follow this thread.…”
Section: Discussionmentioning
confidence: 99%
“…Previously inactivated (56 °C, 30 min) serum samples were serially diluted in culture medium from 1:6 to 1:1458 (3-fold dilution factor), and PRNT 50 was performed in Vero CCL-81 cells (density 200,000 cells/well) cultivated in 24-well plates using the Wuhan strain. The results were expressed in reciprocal serum dilution [ 32 ]. PRNT 50 titers less than 1:10 were considered negative for NAb presence, and the upper limit of quantification of positive samples was 1:1458.…”
Section: Methodsmentioning
confidence: 99%